Heat Shock Proteins: Stimulators of Innate and Acquired Immunity. (25th May 2013) - Colaco, Camilo A.; Bailey, Christopher R.; Walker, K. Barry; Keeble, James
Abstract : Adjuvants were reintroduced into modern immunology as the dirty little secret of immunologists by Janeway and thus began the molecular definition of innate immunity. It is now clear that the binding of pathogen-associated molecular patterns (PAMPs) by pattern recognition receptors (PRRs) on antigen presenting cells (APCs) activates the innate immune response and provides the host with a rapid mechanism for detecting infection by pathogens and initiates adaptive immunity. Ironically, in addition to advancing the basic science of immunology, Janeway's revelation on induction of the adaptive system has also spurred an era of rational vaccine design that exploits PRRs. Thus, defined PAMPs that bind to known PRRs are being specifically coupled to antigens to improve their immunogenicity. However, while PAMPs efficiently activate the innate immune response, they do not mediate the capture of antigen that is required to elicit the specific responses of the acquired immune system. Heat shock proteins (HSPs) are molecular chaperones that are found complexed to client polypeptides and have been studied as potential cancer vaccines. In addition to binding PRRs and activating the innate immune response, HSPs have been shown to both induce the maturation of APCs and provide chaperoned polypeptides for specific triggering of the acquired immune response.